Willingness to act and environmentally conscious consumer behaviour: can prosocial status perceptions help overcome the gap?. (12th September 2012) - Zabkar, Vesna; Hosta, Maja
Abstract Green marketing has not shown expected results in recent years in terms of real changes in behaviours, products and market structures as had been anticipated. Consumer behaviour plays an important role in making these changes happen, and drivers of environmentally conscious consumer behaviour still need to be examined. Concepts of 'concern', 'information about environmental impact' and 'willingness to act' are seen as the key predictors of environmentally conscious consumer behaviours. Although green marketing has been able to address genuinely concerned consumers, additional insights are needed regarding how to appeal to more mainstream consumers. Thus, this paper proposes an extended model of environmentally conscious consumer behaviour in which the gap between willingness to act and actual environmentally friendly consumption is addressed by the moderating role of 'prosocial status' perceptions. In the model, 'concern' is positively related to 'willingness' and both 'willingness' and 'information' are positively related to 'behaviour', while 'prosocial status' perceptions moderate 'behaviour'. The model was verified using a quota sample of 319 general population respondents from a Central European country. According to data, 'prosocial status' perceptions increase the positive association between 'willingness' and 'behaviour' and could be incorporated into green products and advertising to signal personality traits like kindness and intelligence. One possible implication for marketers is that women have a higher average representation in groups of people with high prosocial status perceptions.